The longitudinal study for the work-related factors to job performance among nurses in emergency department. Issue 12 (March 2019) - Chen, Fu-Li; Chen, Kuan-Chen; Chiou, Shy-Yang; Chen, Peter Y.; Du, Man-Li; Tung, Tao-Hsin
Abstract : Abstract: To explore the relationship between baseline information, personal factors, working characteristics and job performance among nurses in emergency department in northern Taiwan. Two-hundred twenty-two nursing staff were interviewed repeated with structured questionnaires for data collection in 3 time points (From August to September, 2008, from February to March, 2009, and from November to December, 2009). The generalized estimating equation (GEE) is used to test the relationship between the domains of independent variables (baseline information, personal factors, working characteristics) and dependent variables (task performance, contextual performance). The mean age of participants is 30.1 ± 5.1 years. 50.0% are junior college or bachelor degrees. From the GEE model, biological protection (β = 0.17, P value = .002) and safety climate (β = 0.24, P value < .001) are significantly related to task performance. Contextual performance is strongly affected by safety climate (β = 0.15, P value < .001). To improve the job performance among nurses in emergency department, it should consider personal psychological and environmental factors.